# Class 11 RD Sharma Solutions – Chapter 1 Sets – Exercise 1.7

**Question 1: For any two sets A and B, prove that: A‘ – B‘ = B – A**

**Solution:**

To prove:Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.A’ – B’ = B – A

Firstly show that

A’ – B’ ⊆ B – A

Let, x ∈ A’ – B’

⇒ x ∈ A’ and x ∉ B’

⇒ x ∉ A and x ∈ B (since, A ∩ A’ = ϕ)

⇒ x ∈ B – A

It is true for all x ∈ A’ – B’

Therefore,

A’ – B’ = B – A

Hence, Proved.

**Question 2: For any two sets A and B, prove the following:**

**(i) A ∩ (A‘ ∪ B) = A ∩ B**

**(ii) A – (A – B) = A ∩ B**

**(iii) A ∩ (A ∪ B’) = ϕ**

**(iv) A – B = A **Δ** (A ∩ B)**

**Solution:**

(i) A ∩ (A’ ∪ B) = A ∩ BHere, LHS A ∩ (A’ ∪ B)

Upon expanding

(A ∩ A’) ∪ (A ∩ B)

We know, (A ∩ A’) =ϕ

⇒ ϕ ∪ (A∩ B)

⇒ (A ∩ B)

Therefore,

LHS = RHS

Hence, proved.

(ii) A – (A – B) = A ∩ BFor any sets A and B we have De-Morgan’s law

(A ∪ B)’ = A’ ∩ B’, (A ∩ B) ‘ = A’ ∪ B’

Take LHS

= A – (A–B)

= A ∩ (A–B)’

= A ∩ (A∩B’)’

= A ∩ (A’ ∪ B’)’) (since, (B’)’ = B)

= A ∩ (A’ ∪ B)

= (A ∩ A’) ∪ (A ∩ B)

= ϕ ∪ (A ∩ B) (since, A ∩ A’ = ϕ)

= (A ∩ B) (since, ϕ ∪ x = x, for any set)

= RHS

Therefore,

LHS = RHS

Hence, proved.

(iii) A ∩ (A ∪ B’) = ϕHere, LHS A ∩ (A ∪ B’)

= A ∩ (A ∪ B’)

= A ∩ (A’∩ B’) {By De–Morgan’s law}

= (A ∩ A’) ∩ B’ (since, A ∩ A’ = ϕ)

= ϕ ∩ B’

= ϕ (since, ϕ ∩ B’ = ϕ)

= RHS

Therefore,

LHS = RHS

Hence, proved.

(iv) A – B = A Δ (A ∩ B)Here, RHS A Δ (A ∩ B)

A Δ (A ∩ B) (since, E Δ F = (E–F) ∪ (F–E))

= (A – (A ∩ B)) ∪ (A ∩ B –A) (since, E – F = E ∩ F’)

= (A ∩ (A ∩ B)’) ∪ (A ∩ B ∩ A’)

= (A ∩ (A’ ∪ B’)) ∪ (A ∩ A’ ∩ B) {by using De-Morgan’s law and associative law}

= (A ∩ A’) ∪ (A ∩ B’) ∪ (ϕ ∩ B) (by using distributive law)

= ϕ ∪ (A ∩ B’) ∪ ϕ

= A ∩ B’ (since, A ∩ B’ = A – B)

= A – B

= LHS

Therefore,

LHS = RHS

Hence, Proved

**Question 3: If A, B, C are three sets such that A ⊂ B, then prove that C – B ⊂ C – A.**

**Solution:**

Given:A ⊂ B

To prove: C – B ⊂ C – ALet’s assume, x ∈ C – B

⇒ x ∈ C and x ∉ B

⇒ x ∈ C and x ∉ A

⇒ x ∈ C – A

Thus, x ∈ C–B ⇒ x ∈ C – A

This is true for all x ∈ C – B

Therefore,

C – B ⊂ C – A

Hence, proved.

**Question 4: For any two sets A and B, prove that**

**(i) (A ∪ B) – B = A – B**

**(ii) A – (A ∩ B) = A – B**

**(iii) A – (A – B) = A ∩ B**

**(iv) A ∪ (B – A) = A ∪ B**

**(v) (A – B) ∪ (A ∩ B) = A**

**Solution:**

(i) (A ∪ B) – B = A – BLet’s assume LHS (A ∪ B) – B

= (A–B) ∪ (B–B)

= (A–B) ∪ ϕ (since, B–B = ϕ)

= A–B (since, x ∪ ϕ = x for any set)

= RHS

Hence, proved.

(ii) A – (A ∩ B) = A – BLet’s assume LHS A – (A ∩ B)

= (A–A) ∩ (A–B)

= ϕ ∩ (A – B) (since, A-A = ϕ)

= A – B

= RHS

Hence, proved.

(iii) A – (A – B) = A ∩ BLet’s assume LHS A – (A – B)

Let, x ∈ A – (A–B) = x ∈ A and x ∉ (A–B)

x ∈ A and x ∉ (A ∩ B)

= x ∈ A ∩ (A ∩ B)

= x ∈ (A ∩ B)

= (A ∩ B)

= RHS

Hence, proved.

(iv) A ∪ (B – A) = A ∪ BLet’s assume LHS A ∪ (B – A)

Let, x ∈ A ∪ (B –A) ⇒ x ∈ A or x ∈ (B – A)

⇒ x ∈ A or x ∈ B and x ∉ A

⇒ x ∈ B

⇒ x ∈ (A ∪ B) (since, B ⊂ (A ∪ B))

This is true for all x ∈ A ∪ (B–A)

∴ A ∪ (B–A) ⊂ (A ∪ B) —(equation 1)

Contrarily,

Let x ∈ (A ∪ B) ⇒ x ∈ A or x ∈ B

⇒ x ∈ A or x ∈ (B–A) (since, B ⊂ (A ∪ B))

⇒ x ∈ A ∪ (B–A)

∴ (A ∪ B) ⊂ A ∪ (B–A) —(equation 2)

From equation 1 and 2 we get,

A ∪ (B – A) = A ∪ B

Hence, proved.

(v) (A – B) ∪ (A ∩ B) = ALet’s assume LHS (A – B) ∪ (A ∩ B)

Let, x ∈ A

Then either x ∈ (A–B) or x ∈ (A ∩ B)

⇒ x ∈ (A–B) ∪ (A ∩ B)

∴ A ⊂ (A – B) ∪ (A ∩ B) —(equation 1)

Contrarily,

Let x ∈ (A–B) ∪ (A ∩ B)

⇒ x ∈ (A–B) or x ∈ (A ∩ B)

⇒ x ∈ A and x ∉ B or x ∈ B

⇒ x ∈ A

(A–B) ∪ (A ∩ B) ⊂ A —(equation 2)

∴ From equation (1) and (2), We get

(A–B) ∪ (A ∩ B) = A

Hence, proved